Influence of alkali metal doping on selectivity behaviour of platinum catalysts for hydrogenation of 2-butyne-1,4-diol - Telkar, M. M.; Rode, C. V.; Rane, V. H.; Chaudhari, R. (Catalysis Communications, 2005)
Hydrogenation of 2-butyne-1,4-diol to 2-butene-1,4-diol (B(2)D) and butane-1,4-diol (B(1)D) using Pt catalysts doped with alkali metals was studied. These catalysts showed higher selectivity to the olefinic diol (B2D) compared to that with monometallic platinum catalyst. Among various alkali metals, Cs-doped catalyst showed highest selectivity (>99%) to B(2)D. The selectivity to B(2)D increased (up to 99.9%) with increase in the concentration of Cs from 0.25% to 1%. The increase in the basic strength of alkali doped catalysts measured by CO(2)-TPD, would be responsible for the increase in electron density of Pt hence, faster desorption and higher selectivity to the intermediate olefinic diol (B(2)D). The reaction parameters; such as temperature, H(2) pressure and substrate concentration haye strong influence on the catalyst activity but almost no effect on the selectivity to B(2)D. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 2-butene-1; 2-butyne-1; 4-diol; alkali metal doping; platinum catalysts; Selective hydrogenation

Stereoselective synthesis of (-)-microcarpalide - Chavan, Subhash P.; Praveen, C. (Tetrahedron Letters, 2005)
A highly convergent and efficient synthesis of (-)-microcarpalide, a 10-membered lactone displaying remarkable microfilament disrupting activity is described. Ring-closing metathesis and Sharpless asymmetric dihydroxylations are the key steps. Our strategy highlights the application of novel hydroxy lactone precursors for the stereoselective synthesis of (-)-microcarpalide. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: 4-diol; cis-2-butene-1; Claisen ortho ester rearrangement; microcarpalide; Ring-closing metathesis; sharpless asymmetric dihydroxylation

Catalytic hydrogenation of 2-butyne-1,4-diol: activity, selectivity and kinetics studies - Rode, Chandrashekhar V. (Journal of the Japan Petroleum Institute, 2008)
The reaction pathway for hydrogenation of 2-butyne-1,4-diol involves parallel and consecutive isomerization as well as hydrogenation reactions forming other side products along with cis-2-butene-1,4-diol and butane-1,4-diol. Hence, achieving the highest selectivity to butene- and/or butanediol is critical from industrial point of view. Hydrogenation of butynediol is also of fundamental significance, due to its adsorption characteristics leading to the formation of active species and their role in determining the product distribution. Studies on designing various catalyst systems including colloidal as well supported palladium nanoparticles for the hydrogenation of butynediol, role of additives, catalyst pretreatment, kinetic studies carried out in our group has been presented in this review. Interestingly, almost complete selectivity to the intermediate olefinic diol was achieved with 1% Pd/CaCO3-NH3 catalyst system. This could be due to the competitive adsorption of ammonia on the palladium surface along with the substrate 2-butyne-1,4-diol. Studies on catalyst pretreatment and kinetics using palladium catalyst have also been presented here. Nanostructure palladium both colloidal as well as supported catalysts showed a very high catalytic activity (10-40 times more) in the hydrogenation 2-butyne-1,4-diol to cis-2-butene-1,4-diol compared with the corresponding conventional Pd catalysts. For platinum based catalysts, formation of side products was completely eliminated in the hydrogenation of butyne diol. The increase in the basic strength of alkali metal doped Pt catalysts measured by CO2-TPD, led to the increase in electron density of Pt hence, faster desorption and higher selectivity to butenediol. In the case of continuous hydrogenation, the selectivity pattern was completely different from that found in the case of batch slurry reactor and by varying the contact time, the selectivity to both butene- and butanediols could be varied over a wide range of conditions.
Keywords: 2-butene-1; 2-butyne-1; 4-diol; alkali metal doping; catalyst pretreatment; nano palladium catalyst; Selective hydrogenation